A38: Twelve Years' Experience with Etanercept in the Treatment of Juvenile Idiopathic Arthritis: How It Has Changed Practice—The German Biologics JIA Registry (BiKeR). Issue Volume 66:Issue(2014)supplement 3 (March 2014) - Schmeling, Heinrike; Minden, Kirsten; Foeldvari, Ivan; Haas, Johannes‐Peter; Hospach, Anton; Horneff, Gerd
Abstract : Background/Purpose: The outcome of children with JIA refractory to disease‐modifying antirheumatic drugs (DMARDs) has improved significantly since Etanercept became available. The objectives were to analyse data from the German Biologics JIA Registry (BiKeR) and to report on practice changes of the last twelve years. Methods: Baseline demographics, pre‐treatment, concomitant treatment, clinical characteristics and disease activity parameters and outcome have been prospectively documented in BiKeR since 2000. Efficacy was determined using the PedACR response criteria, the JADAS‐10 and the proposed criteria for inactive disease on medication. Results: From 2000 to 2012 1678 children with JIA on Etanercept with a total of 11, 474 visits have been enrolled in BiKer (3424.2 total patient‐years). The median disease duration at treatment start decreased from 4.5 to 2 years. While initially children have been pre‐treated with numerous antirheumatic agents, including cytotoxic agents, pre–treatment markedly decreased by a mean 6.3 (median 4.3) to 0.99 (median 1.0) DMARDssol;patient. Concomitant treatment initially consisted of corticosteroids in 83%, Methotrexate in 95% and other DMARDs in 45% of children compared to 40%, 74% and 6.7% respectively in 2012. At Registry start, 26% of newly enrolled children belonged to the systemic JIA category compared to only 1% in 2012. In contrast, the rate of children with enthesitis related arthritis increased from 2% to 16%. The median JADAS‐10 in 2000 compared to 2012 was significantly higher at treatment start (24.4+/−6.8 vs. 13.3+/−6.2) and remained higher after 6 months on treatment (7.5+/−7.2 vs. 4.5+/−5.2). The number of patients that have reached a PedACR 70 after 12 months on treatment increased from 41% starting in 2000 to 51% of patients starting in 2012. Inactive disease within one year was documented initially in 20% of children and increased to 43% in 2012. Conclusion: In recent years, children with JIA have been treated earlier, received less pre‐ and concomitant treatment with corticosteroids as well as with DMARDs. Patients have shown a markedly better outcome reflected in the higher PedACR response, lower JADAS‐10 and higher rate of patients with inactive disease after one year on treatment. These data suggest that early disease control and better pre–selection of patients who need biologics are important to improve outcome in children with JIA.